(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
We survey the literature on how small businesses in the United States finance themselves. Our results demonstrate the important role that the financial services industry, particularly bank credit, plays in the capital structure of small firms. The results also reinforce the importance of owner equity as a primary source of financing. This article examines the economics of nancing small business in private equity and debt markets. Firms are viewed through a nancial growth cycle paradigm in which different capital structures are optimal at dierent points in the cycle. We show the sources of small business finance, and how capital structure varies with firrm size and age.